The Relationship between Website Design Quality and Online Purchase Intention - Mahzan, Nurul Azira; Salim, Siti Aisyah (Research in Management of Technology and Business, 2023)
Online shopping is a type of e-commerce in which customers can purchase goods or services directly from a seller via the Internet. The demand for customers to buy through online websites is strongly influenced by several website qualities which encourage them to search for and buy the product. However, despite the importance of website design qualities, there is still a lack of studies investigating the relationship between website design quality with online purchase intention. Meanwhile, consumers are evaluating the various features and services offered by e-commerce websites as they become more aware of their value. Hence, this study aims to understand the relationship between website design quality and online purchase intention. This study has employed quantitative research that include questionnaires and an online survey. The Statistical Package for Social Science (SPSS) has been used to analyze quantitative reports. This study will help marketers or sellers in understanding the best marketing strategy for developing the best website design quality to adopt, particularly for younger users. As the result, all the respondents agreed that website design quality has a significant relationship with online purchase intention even though the correlation with the variables was weak.